X-ray fluorescence data of core MD-3 in florida mangrove diebacks - Cohen, Marcelo Cancela Lisboa (In: Cohen, MCL (2024): Florida mangrove diebacks [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.964591, 2024)
Concentration (ppm) of some chemical elements in coastal sediments obtained along core MD-3, representing marine (e.g. Br, Ca, Cl, and Sr) and terrestrial (e.g. Fe, Ti, and Mn) sources. X-ray fluorescence analysis was carried out at 2 cm intervals using an Innov-X Delta XRF. Units in ppm.
Keywords: carbon isotope; dieback; Florida; mangrove